An insight on Biocathode Microbial Desalination Cell: Current challenges and prospects. (22nd February 2022) - Prakash, Sandhya; Ponnusamy, Kalaichelvi; Naina Mohamed, Samsudeen
Summary: Microbial Desalination Cell (MDC) is an emerging sustainable technology that offers the significant advantage of simultaneous electricity generation, water desalination, and pollutants removal such as chemical oxygen demand (COD), biological oxygen demand (BOD), total dissolved solids (TDS), color, etc. from industrial or domestic wastewater. The current MDC technology primarily utilizes conventional (chemical) cathode for maximum power output and desalination efficiency, which is unsustainable and toxic to the environment. Utilization of biocathode in MDC is economically, environmentally, and socially sustainable due to reduced operation cost, eco‐friendliness, stability for long‐run over chemical electrodes, and efficient pollutant removal from wastewater, which in turn creates a pollution‐free environment for the society. In biocathode MDC, bacteria, yeast, fungi, or algae acts as a catalyst for reduction reaction by forming biofilm at the cathode, which avoids the use of expensive metal catalysts and eliminates the toxicity produced by the chemical cathodes. Microalgae as a biocathode has the ability to provide four times the dissolved oxygen concentration by photosynthesis than that obtained by pumping external air. Hence, power output is increased on using microalgae, and meanwhile, energy consumption is zero. Although there are exceptional benefits, biocathode is underutilized since research contribution towards the use of diverse microorganisms as biocathode is yet to be improved. This review gives an intelligible picture on the importance of biocathode over other cathodes, microbial community and materials used, other applications, and downside of biocathode in MDC. Abstract : Electricity from wastewater by microorganisms in MDC is used for desalination. Chemical and air cathodes are unsustainable, toxic, and expensive on a large scale. Biocathodes replace the toxic, expensive metal catalysts and improve desalination. Microalgal biocathodes eliminate the aeration need, useful in large‐scale studies. The algal biomass can be used for producing biofuel, feed, and pharmaceuticals.